The Reform Path of Physical Education Curriculum in Chinese Basic Education - Jiang, Bo; Wang, Shaojie; Fu, Yao; Xiang, Jinbo; Chen, Qiuyi (Quality in Sport, 2024)
This research takes the path of PE curriculum reform in basic education as the research object, and makes a profound analysis of the present situation of PE curriculum reform in basic education by the method of literature. The research shows that there are four problems in the current PE curriculum reform of basic education in China: the theoretical basis fails to reach consensus, the PE teaching conditions do not meet the development needs of PE curriculum reform, the concept and importance of the leadership in charge of PE curriculum reform is not high, and the lack of vertical promotion mechanism in the implementation of PE curriculum. The research value lies in: On the basis of inheriting and learning from, we should carry out the spirit of the 20th National Congress of the Communist Party of China, implement the fundamental task of cultivating morality and educating people, and do a good job of education that satisfies the people. We should reposition and innovate the concept, system, teaching method and course content of physical education curriculum in our current schools, and consider the direction of physical education curriculum reform and optimization in our basic education schools. Let the students get physical and mental health, social skills and sports morality in the physical education classroom and life.